Atomic level spatial variations of energy states along graphene edges - Warner, J; Lin, Y; He, K; Koshino, M; Suenaga, K (American Chemical Society, 2014)
The local atomic bonding of carbon atoms around the edge of graphene is examined by aberration-corrected scanning transmission electron microscopy (STEM) combined with electron energy loss spectroscopy (EELS). High-resolution 2D maps of the EELS combined with atomic resolution annular dark field STEM images enables correlations between the carbon K-edge EELS and the atomic structure. We show that energy states of graphene edges vary across individual atoms along the edge according to their specific C-C bonding, as well as perpendicular to the edge. Unique spectroscopic peaks from the EELS are assigned to specific C atoms, which enables unambiguous spectroscopic fingerprint identification for the atomic structure of graphene edges with unprecedented detail.